Pengaruh Leadership terhadap Performance Karyawan: A Literature Review - Paskah Magdalena; Jesica Tri Agita; Feronica Simanjorang (ARIMA : Jurnal Sosial Dan Humaniora, 2023)
Every company or organization faces challenges in enhancing the quality of its human resources. In an effort to improve the quality of human resources, organizations need to create a healthy work environment accompanied by effective leadership behavior to assist employees in staying motivated and performing better. The objective of this research is to examine the influence of leadership styles on employee performance in a company. The method used in this research is a literature review, with data gathered from several previous journals by reviewing ten journals from various databases. The results of this review indicate a significant impact of leadership styles on employee performance within an organization.